Platelet Morphological Assessment Based on Shelf-Life of Concentrated Platelet Components - Dewi Astuti; Eva Ayu Maharani; Hafshoh Susadma (Biomedika, 2021)
Concentrated platelet components are the components or platelets that are processed through centrifugation from whole blood or a single donor. The components of the concentrate platelets are stored in an agitator at a temperature of 20-24◦C with a maximum shelf-life of five days. During the storage, a change in component metabolism occurs, which is characterized by alteration in platelet morphology as an indicator of decreasing quality of platelet components. The purpose of this study was to determine the quality of the components of platelets based on the shelf-life by measuring the platelet morphological values with the Kunicki method. This study applied an experimental method by conducting inspections of the regional blood transfusion unit (UTDD) of the Indonesian Red Cross of Jakarta Capital Special Region (PMI DKI Jakarta). Platelet morphological values of six components of platelets were examined by the Kunicki method on day 0 to day 5 of shelf-life. Quality assessment was carried out based on a significant difference-dependent t-test and comparison with normal value. The results of the study by performing statistical analysis of the significant difference-dependent t-test showed a significant difference of values between day 0 and day 1 to day 5 of shelf-life. Comparison with normal values ​​depicted that all samples stored on day 4 had a morphological value of more than 200. On day 5 of shelf-life, the platelet morphology values ​​of five samples were below 200. The quality of the concentrated platelet components is said “good” if it is above 200. This study concluded that there was a significant difference in the platelet morphology values between the components of concentrated platelets on day 0 and day 1 to day 5 of shelf-life. All samples were of good quality until day 4 of storage. However, on day 5 of storage, only one sample was good in quality.